Fuel and thermal NO formation during black liquor droplet pyrolysis with envelope flame. (1st July 2020) - S.P. da Silva, Paulo; Engblom, Markus; Brink, Anders; Hupa, Leena
Abstract: The behaviour of black liquor nitrogen under pyrolysis with envelope flame was investigated with experiments in single-particle combustion with measurements of CO and CO 2 and NO. Char carbon and nitrogen retention after pyrolysis were also measured with CHNS analysis of char residue. The combustion environment had a temperature from 800 °C to 1000 °C with 0% to 15% O 2 in N 2 or Ar with a droplet size of 10 mg. Also, gas phase simulations of the enveloping flame surrounding the black liquor droplet using FLUENT and CHEMKIN software with detailed chemistry were also conducted to understand nitrogen volatile chemistry better. Thermal NO was observed at 1000 °C with O 2 concentrations above 10% and at 900 °C with 15% O 2 . Fuel nitrogen conversion to NO averaged 25% of black liquor nitrogen. Simulations showed that the unaccounted nitrogen fraction in experimental results is most likely reduced to N 2 . A previously developed CFD boiler model was used to assess how much of black liquor pyrolysis occurs in conditions found to be conducive to thermal NO. Only 0.05% of black liquor droplets would pyrolyze in conditions were thermal NO would form. The boiler model also showed that 30% of black liquor droplets would pyrolize with an envelope flame, which makes fuel nitrogen reach the bulk gas phase of the recovery boiler as NO and N 2 instead of NH 3 .